Rofecoxib Attenuates the Pathogenesis of Amyotrophic Lateral Sclerosis by Alleviating Cyclooxygenase-2-Mediated Mechanisms - Yan-Hui Zou; Pei-Pei Guan; Shen-Qing Zhang; Yan-Su Guo; Pu Wang (Frontiers in Neuroscience, 2020)
Cyclooxygenase-2 (COX-2) is reported to be activated during the course of amyotrophic lateral sclerosis (ALS) development and progression. However, the roles of COX-2 in aggravating ALS and the underlying mechanism have been largely overlooked. To reveal the mechanisms, the canonical SOD1G93A mouse model was used as an experimental model for ALS in the current study. In addition, a specific inhibitor of COX-2 activity, rofecoxib, was orally administered to SOD1G93A mice. With this in vivo approach, we revealed that COX-2 proinflammatory signaling cascades were inhibited by rofecoxib in SOD1G93A mice. Specifically, the protein levels of COX-2, interleukin (IL)-1β, and tumor necrosis factor (TNF)-α were elevated as a result of activation of astrocytes and microglia during the course of ALS development and progression. These proinflammatory reactions may contribute to the death of neurons by triggering the movement of astrocytes and microglia to neurons in the context of ALS. Treatment with rofecoxib alleviated this close association between glial cells and neurons and significantly decreased the density of inflammatory cells, which helped to restore the number of motor neurons in SOD1G93A mice. Mechanistically, rofecoxib treatment decreased the expression of COX-2 and its downstream signaling targets, including IL-1β and TNF-α, by deactivating glial cells, which in turn ameliorated the progression of SOD1G93A mice by postponing disease onset and modestly prolonging survival. Collectively, these results provide novel insights into the mechanisms of ALS and aid in the development of new drugs to improve the clinical treatment of ALS.